2018
DOI: 10.1037/apl0000283
|View full text |Cite
|
Sign up to set email alerts
|

The dimensions and mechanisms of mindfulness in regulating aggressive behaviors.

Abstract: On the basis of the notion that the ability to exert self-control is critical to the regulation of aggressive behaviors, we suggest that mindfulness, an aspect of the self-control process, plays a key role in curbing workplace aggression. In particular, we note the conceptual and empirical distinctions between dimensions of mindfulness (i.e., mindful awareness and mindful acceptance) and investigate their respective abilities to regulate workplace aggression. In an experimental study (Study 1), a multiwave fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 97 publications
4
82
0
1
Order By: Relevance
“…Perhaps the ability of mindful individuals to take an open, non-judgmental stance and to disengage from ego-identification allows them to make a less reactive, more balanced assessment of others' behaviour, and thus be more willing to engage with others without fear of being "cheated." This explanation is consistent with previous research indicating that mindfulness can reduce aggression (Liang et al, 2018) and reactions to perceived injustice (Long & Christian, 2015) in the workplace; and with brain-imaging studies that suggested that mindfulness meditators were better able to subdue emotional reactions to unfair social exchange (Kirk et al, 2011). Alternatively, it may be that the increase in positive affect and wellbeing brought about by mindfulness provides greater emotional resources, increasing individuals' willingness to engage in TMX (Barnes et al, 2007;Singh, Lancioni, Winton, Karazsia, & Singh, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Perhaps the ability of mindful individuals to take an open, non-judgmental stance and to disengage from ego-identification allows them to make a less reactive, more balanced assessment of others' behaviour, and thus be more willing to engage with others without fear of being "cheated." This explanation is consistent with previous research indicating that mindfulness can reduce aggression (Liang et al, 2018) and reactions to perceived injustice (Long & Christian, 2015) in the workplace; and with brain-imaging studies that suggested that mindfulness meditators were better able to subdue emotional reactions to unfair social exchange (Kirk et al, 2011). Alternatively, it may be that the increase in positive affect and wellbeing brought about by mindfulness provides greater emotional resources, increasing individuals' willingness to engage in TMX (Barnes et al, 2007;Singh, Lancioni, Winton, Karazsia, & Singh, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Hülsheger et al (2013) also found that both dispositional and state mindfulness were related to higher job satisfaction and lower emotional exhaustion among service workers, and that these relationships were mediated by emotion regulation. As previously discussed, there is also evidence for the benefits of mindfulness via emotion regulation for employees managing injustice (Long & Christian, 2015) and for leaders in managing responses to hostility and poor subordinate performance (Liang et al, 2018). In consideration of this research we therefore predict:…”
Section: Mindfulness and Emotion Regulationmentioning
confidence: 71%
See 2 more Smart Citations
“…Moreover, the wider the gap between organizational display rules and workers' genuine emotions, the less inclined workers may be to identify with their job, leading them to experience reduced levels of job satisfaction and an increased sense of psychological disconnection from their work (Heider, 1946). Such feelings of inauthenticity may make them less likely to experience healthy levels of psychological detachment and more likely to have sleeping problems given the links between surface acting and rumination (Liang et al, 2018).…”
Section: Outcomes Of Emotional Labor Profilesmentioning
confidence: 99%